Closed loop price signal based market operation within Microgrids - Gan, Chin Kim (John Wiley & Sons, Ltd., 2011)
Within a general Microgrid framework, this paper presents a model to simulate closed loop energy and ancillary services markets operated by a Microgrid Central Controller (MGCC) and to investigate the performance of such a market mechanism in managing disturbances both within and outside the Microgrid cell. The proposed approach can be seen as an alternative to a more traditional control approach in which the central operator optimises the dispatch of all generators taking into account their bids and then instructing them to produce their outputs at the specified prices according to merit order and network constraints. In the alternative approach discussed here, this dispatch decision is decentralised to each controllable unit. The central operator only influences the decision taken by each unit via price signals. The main advantage of the approach is to preserve the independency of the local controllers and to decentralise the operation decision, making the system more able to cope with a large number of generating units. The performance of the proposed market mechanism is examined via different case studies that simulate the control actions of MGCC, micro-sources and controllable loads in managing small and large disturbances within and outside the Microgrid cell.